Immune Checkpoint Inhibitor-Induced Liver Injury - Gudd, Cathrin L.C.; Sheth, Roosey; Thursz, Mark R.; Triantafyllou, Evangelos; Possamai, Lucia A. (Seminars in Liver Disease, 2023)
In recent years cancer treatment has been revolutionized by the development and wide application of checkpoint inhibitor (CPI) drugs, which are a form of immunotherapy. CPI treatment is associated with immune-related adverse events, off-target tissue destructive inflammatory complications, which may affect a range of organs, with liver inflammation (hepatitis) being one of the more commonly noted events. This is a novel form of drug-induced liver injury and a rapidly evolving field, as our understanding of both the basic immunopathology of CPI hepatitis (CPI-H) and optimal clinical management, races to catch up with the increasing application of this form of immunotherapy in clinical practice. In this review, we summarize current evidence and understanding of CPI-H, from fundamental immunology to practical patient management.
Keywords: checkpoint inhibitor; immunotherapy; liver injury; hepatotoxicity